ВРАХУВАННЯ МЕРЕЖЕВИХ ОБМЕЖЕНЬ ТА МІНІМІЗАЦІЯ РІЗНИЦІ ЦІН МІЖ РИНКАМИ ЕЛЕКТРОЕНЕРГІЇ - Блінов , І.В.; Парус , Є.В. (Інститут електродинаміки НАН України, Київ, 2015)
Article is devoted to the task of congestion management of the electric intersystem communication during trading on the day-ahead market. The main problems of methods usage of Flow-Base Market Coupling, Decentralized Market Coupling and Trilateral Market Coupling to solve the problem are briefly described. The method of indirect accounting network constraints on the "day-ahead" market is described. It is a development of the Decentralized Market Coupling with the formal presentation of the electric network structure and taking into account the non-linear character of the mathematical model, which used to solve the problem. The methods of formalized representation of the electric network structure are shown. The choice of the objective function to solve the problem is corroborated. The task of congestion management in this method is to minimize the difference of clearing prices between the coupling electricity markets. The basic equation constraints, reflecting the balance of supply and demand, as well as the balance of power exchanges between these markets are described. The method of the organization of the iterative process for solving this problem for any number of coupling markets is shown. The method of indirect accounting network constraints on the "day-ahead" market use the minimizing the difference of clearing prices between the coupling markets and has well formalized apparatus of net exports functions, which is the base of Decentralized Market Coupling method. As distinct from the latter, the proposed method performs iterative approximation to a sustainable solution for any number of coupling electricity markets with an arbitrary structure of electrical connections between them and takes into account different discrete and linear types of bids and offers from market participants. References 9, figures 2.